DIGITAL FREE TOURISM: STRATEGY FOR DEVELOPING TOURISM IN INDONESIA - Indra Permana; Tono Mahmudin; Nourma Wulanda; Riki Adriant; Eva Yuniarti Utami (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research aims to (1) describe the potential of digital free in developing Indonesian tourism; and (2) know the strategy for developing Indonesian tourism through digital free. This research uses SWOT analysis. The results of this research show that (1) the digital free concept is considered appropriate to be applied in several natural destinations in Indonesia that have limited internet access; (2) strategies for developing Indonesian tourism through digital free based on SWOT analysis, including SO strategy through promoting digital free tourism to the public, WO strategy by developing the concept of digital free tourism to attract tourists, ST strategy through collaboration with tourism stakeholders to provide digital free tourism, and WT strategy through educating tourism managers to develop digital free tourism. Keywords: Digital free, tourism, develop